Acute intermittent porphyria presenting with posterior reversible encephalopathy syndrome (PRES) and abdominal pain. Issue 6 (17th June 2020) - Swart, Grace; Lim, Su San; Jude, Martin
Abstract : Acute intermittent porphyria is a rare genetic condition in which disrupted haem synthesis causes overproduction of porphyrin precursors. Occasionally, it is associated with posterior reversible encephalopathy syndrome (PRES), presenting with headache, confusion, seizures and visual disturbance. We describe a patient with acute intermittent porphyria who presented with seizures and PRES, and who had previous unexplained severe abdominal pain. Acute intermittent porphyria should be considered as a possible cause of PRES, especially in those with unexplained abdominal pain, since delays in its diagnosis can result in permanent complications.